“You Kind of Have to Bite the Bullet and do Bitch Work”: How Internships Teach Students to Unthink Exploitation in Public Relations - Michelle Rodino-Colocino; Stephanie N. Berberick (tripleC: Communication, Capitalism & Critique)
Based on critical analysis of three focus groups with PR students at Penn State, we argue that describing PR internships as “bitch work” highlights key material and ideological lessons about labour, gender, and exploitation. Analysing interviews of PR interns through Marxist and feminist perspectives, we explain the dynamics of viewing PR internships as “bitch work.” We discuss how internships come to signify good luck in a lottery-like market while also instilling a love of work and the hope that “good work” will follow “bitch work.” Such lessons, furthermore, teach interns to unthink work, our phraseology for the ideological process of viewing internships as almost-but-not-quite labour. We conclude with a call to rethink internships as work, recognize the gendered exploitation of interns, and compensate interns for their real labour.